Financial characteristics of companies in failure situation in Morocco - NOKAIRI, Wafia (Revue du contrôle, de la comptabilité et de l’audit, 2020)
The failure of the companies touches several disciplinary fields. The concept is analyzed under three aspects: economic, legal and financial. Its origins and its causes can be very different but they reflect all on the financial statement of the company. In general, the failure is defined by the incapacity of a company to honor its financial liabilities with respect to its creditors, in particular the bank. So the consequences of a failure remain very heavy. The purpose of this article is to highlight the principal indicators of fragility of these companies. We aim to draw, through a sample of Moroccan companies, the profile of the failing companies through the analysis of the evolution of their principal financial indicators over three years preceding their failure, while comparing them with the indicators of healthy companies. Our study focused on a sample of 200 Moroccan companies, including 100 failing and 100 healthy. The objective is to understand the financial characteristics of failing compagnies and the factors which discriminate most between these two types of companies.